2018
DOI: 10.1007/s10943-018-0570-x
|View full text |Cite|
|
Sign up to set email alerts
|

Black Male Mental Health and the Black Church: Advancing a Collaborative Partnership and Research Agenda

Abstract: This article explores the role the Black Church could play in facilitating spiritually sensitive, culturally relevant and gender-specific services to address the mental health and well-being of Black males. The help-seeking behaviors of Black men are examined as the authors offer two theories: the body, mind, spirit, environment, social, transcendent, and health, illness, men, and masculinities that may assist the Black Church in functioning as an effective support networks for healthy Black male mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…There are some preexisting examples of successful Black Church and health professional collaborations. For instance, Robinson et al (2018) highlighted the stressors faced by Black men and the disparities in attending to mental health. The authors suggested that Black churches provide a safe, accessible space for mental health professionals, Black pastors, and leaders to host trainings and educational mental health fairs.…”
Section: The Black Churchmentioning
confidence: 99%
See 2 more Smart Citations
“…There are some preexisting examples of successful Black Church and health professional collaborations. For instance, Robinson et al (2018) highlighted the stressors faced by Black men and the disparities in attending to mental health. The authors suggested that Black churches provide a safe, accessible space for mental health professionals, Black pastors, and leaders to host trainings and educational mental health fairs.…”
Section: The Black Churchmentioning
confidence: 99%
“…The authors gleaned important perceptions about depression; however, they also recommended CBPR in integrating mental health programming and testing their effectiveness. Although scholars, such as Dempsey et al (2016) and Robinson et al (2018), have provided a strong foundation for collaborations between counseling professionals and Black churches, there remains a need for additional guidance on how to carry out these partnerships.…”
Section: The Black Churchmentioning
confidence: 99%
See 1 more Smart Citation
“…32 , 33 Each dimension has been associated with the survival of blacks 34 , 35 and, in particular, black men. 26 , 36 , 37 Faith-based institutions have been regarded as sacred and safe places where males are welcomed and given affirmative spiritual messages that serve as the foundation of religious coping resources in the face of stressful social environments and situations. 35 , 38 Numerous studies have examined the impact of religious coping on variety a of health outcomes over the past 3 decades 39 - 41 ; yet, remarkably few examine the degree to which faith-oriented resources can reduce racial disparities in outcomes associated with prostate cancer and other chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Hays & Aranda, 2016;Holt et al, 2017;Jones et al, 2018;Watlington & Murphy, 2016). A gap in the literature existed regarding the described experience of the African American adult who seeks the church for support through religion and spirituality after the violent death of a family member (Gonzalez et al, 2009;Park et al, 2018;Robinson et al, 2018;Wilson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%